PENANAMAN NILAI NASIONALISME MELALUI PARAFRASE BIOGRAFI LETNAN JENDERAL JAMIN GINTING PADA SISWA SMP NEGERI 3 KABANJAHE KABUPATEN KARO - Ginting, Pivi Turbana Br; Teguh Trianton; Wahyu Ningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to Cultivate the Value of Nationalism Through Paraphrasing the Biography of General Lieutenant Jamin Ginting in class IX students of SMP Negeri 3 Kabanjahe. The method of paraphrasing the biography of Lieutenant General Jamin Ginting to improve students' writing skills can increase students' insight into the biography of national heroes applied in Indonesian language learning. The population in this study were Indonesian language teachers and ninth grade students of SMP Negeri 3 Kabanjahe from class IX-1. The total population was 30 students. This qualitative data is obtained from observation, interview and documentation data. The results of the study found that efforts to increase insight into the biography of Lieutenant General Jamin Ginting in students and improve writing skills by paraphrasing the biography of Lieutenant General Jamin Ginting. Suggestions to foster a strong sense of nationalism among the younger generation. Paraphrasing biographies of struggle figures can be an effective means of strengthening love for the country and introducing national values to students.